The Mockingbirds - Whitney, Daisy (New York : Little, Brown and Co., 2010)
When Alex, a junior at an elite preparatory school, realizes that she may have been the victim of date rape, she confides in her roommates and sister who convince her to seek help from a secret society, the Mockingbirds.
Keywords: Date rape -- Fiction; Secret societies -- Fiction; Justice -- Fiction; Boarding schools -- Fiction; Schools -- Fiction; Sisters -- Fiction